Agronomic Performance and Yield Stability of the RNA Interference‐Based Bean golden mosaic virus‐Resistant Common Bean. Issue 2 (1st March 2018) - Souza, Thiago Lívio P. O.; Faria, Josias C.; Aragão, Francisco J. L.; Del Peloso, Maria J.; Faria, Luis C.; Wendland, Adriane; Aguiar, Marcelo S.; Quintela, Eliane Dias; Melo, Carlos Lásaro P.; Hungria, Mariangela; Vianello, Rosana P.; Pereira, Helton S.; et al.
Abstract : Bean golden mosaic virus (BGMV) causes the main common bean ( Phaseolus vulgaris L.) viral disease in Brazil, causing yield losses of 40 to 100%. Effective resistance to BGMV has not been identified in common bean lines tested in Brazil. Therefore, Embrapa used a transgenic approach to develop effective resistance to BGMV (event Embrapa 5.1), using RNA interference and plant transformation through the biolistic method. In the present work, we evaluate the agronomic performance and yield stability of 10 transgenic BGMV‐resistant common bean elite lines from the carioca market class in 31 field trials conducted in Brazil from 2012 to 2014 to identify superior line suitable for release as a new cultivar. The results showed that the presence of the transgene did not cause any loss in yield and conferred greater yield stability in the transgenic elite lines because of the resistance to BGMV. The first commercial product developed with the BGMV resistance was selected, the line CNFCT 16205 (cv. BRS FC401 RMD), which is also the first genetically modified common bean cultivar developed in the world. The line exhibited high yield potential and stability, standard commercial seeds, a normal growing cycle (85–94 d), and effective resistance to BGMV. In addition, it has moderate resistance to anthracnose. However, it is susceptible to Cowpea mild mottle virus (CPMMV). BRS FC401 RMD can contribute to the sustainability of the common bean crop in Brazilian agriculture sector, and to the stability in the supply and price of common bean in the domestic market.